Interplay of dynamical and explicit chiral symmetry breaking effects on a quark - Serna, Fernando E. [UNESP]; Chen, Chen [UNESP]; El-Bennich, Bruno [UNESP] (American Physical Society (APS), 2019)
The relative contributions of explicit and dynamical chiral symmetry breaking in QCD models of the quark-gap equation are studied in dependence of frequently employed Ansätze for the dressed interaction and quark-gluon vertex. The explicit symmetry breaking contributions are defined by a constituent-quark sigma term whereas the combined effects of explicit and dynamical symmetry breaking are described by a Euclidean constituent-mass solution. We extend this study of the gap equation to a quark-gluon vertex beyond the Abelian approximation complemented with numerical gluon- and ghost-dressing functions from lattice QCD. We find that the ratio of the sigma term over the Euclidean mass is largely independent of nonperturbative interaction and vertex models for current-quark masses, mu,d(μ)≤m(μ)≤mb(μ), and equal contributions of explicit and dynamical chiral symmetry breaking occur at m(μ)≈400 MeV. For massive solutions of the gap equation with lattice propagators this value decreases to about 220 MeV.